Environmental Factors Influencing Career Switch Intention among Mass Communication Professionals in Southwest Nigeria - Onyeizu, Ajaegbu Oguchi; Olayinka, Awofadeju Peter (Advances in Social Sciences Research Journal, 2020)
This paper seeks to examine the environmental factors such that influence career switch intention among mass communication professionals in the South-Western region of Nigeria. The paper sets out four perspectives on the likely causes of career change: job condition, job training, social factors, and economic factors, which link respectively to the literatures on the causes of career switch from one field of professionalism (or job) to another. Survey research design was used while questionnaire was the instrument employed in collection of data. Findings revealed that career switch intention among mass communication professionals in Southwest Nigeria was influenced to a very large extent by environmental factors such as irregular salary payment, poor job condition, bad treatment of staff, etc.